2019
DOI: 10.1177/1557988319851616
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ Experiences and Perspectives of Breastfeeding: A Scoping Review

Abstract: During the transition to parenthood, fathers may experience significant challenges, including finding a place for themselves as important participants in the context of infant breastfeeding by female partners. Although generally viewed as a healthy process and the preferred method of infant feeding, breastfeeding may result in some fathers feeling excluded, inadequate, and helpless. Breastfeeding is known to adversely affect various aspects of a father’s life, including parenting self-efficacy, quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
(184 reference statements)
2
44
0
1
Order By: Relevance
“…Two randomized controlled trials showed how educating fathers for the role of "breastfeeding coach" has positive effects on breastfeeding in terms of increased initiation rate, reduced worry about low milk supply, and reduced premature breastfeeding cessation [13,30]. Moreover, in a recent review, Sihota et al highlighted the need for comprehensive antenatal support and education tailored for fathers of breastfed infants [31]. Interestingly, some Authors have reported how fathers themselves want to know more about breastfeeding [13,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two randomized controlled trials showed how educating fathers for the role of "breastfeeding coach" has positive effects on breastfeeding in terms of increased initiation rate, reduced worry about low milk supply, and reduced premature breastfeeding cessation [13,30]. Moreover, in a recent review, Sihota et al highlighted the need for comprehensive antenatal support and education tailored for fathers of breastfed infants [31]. Interestingly, some Authors have reported how fathers themselves want to know more about breastfeeding [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent review, Sihota et al highlighted the need for comprehensive antenatal support and education tailored for fathers of breastfed infants [31]. Interestingly, some Authors have reported how fathers themselves want to know more about breastfeeding [13,31]. The majority of fathers enrolled stated they had received su cient information either before their baby's birth or during the hospital stay or at discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Father's participation in different reproductive stages including prenatal, parturition, postpartum and neonatal care were studied. One of the most important roles of fathers is their support of breastfeeding mothers (17,18). Fathers' participations demonstrated to be related with success and continuity of breastfeeding (19,20).…”
Section: Introductionmentioning
confidence: 99%